Effect of ZnO NPs on Ovarian Histological Structure and Function in Adult Female Rats (Baghdad Science Journal, 2024)
Nanotechnology is one of the most important techniques that is widely used in many fields by changing the physical and chemical properties of materials to form new scale substances called nanoparticles to make them more effective. ZnO NPs is one of these particles that is used in multiple applications, especially in cosmetic and sunscreen products. Thus, the uses of these particles in great quantities make them in constant contact with the body and can enter the circulating blood in a different ways. The aim of this study was to find out the effect of ZnO NPs on the histological structure and functions of the ovary, as well as to determine the levels of gonadotropin hormones (FSH and LH). Therefore, 54 adult female rats were randomly divided into three primary groups according to the duration of exposure (1, 2, and 4 weeks). These groups were then further divided into three subgroups, each of which consisted of six rats, one of which served as a control group and was injected with 1 ml of distilled water, while the others served as treated groups and were injected with 1 ml of ZnO NPs at low and high concentrations 50 and 200 mg/kg respectively, an average of three intra-peritoneal injections per week. The results showed different histological changes in the ovarian tissue sections of treatment rats at different doses and durations, as well as significant decrease (p≤ 0.01) in the levels of estrogen, progesterone, LH, and FSH hormones in treated animals at different doses and durations. It can be concluded that the ZnO NPs have ability to damage the ovarian tissue, and disruption of its cellular functions that caused an imbalance in reproductive hormones levels (P and E2, LH and FSH).